Novel hydrogels based on yeast chitin-glucan complex: Characterization and safety assessment - Araújo, Diana (2020)
Chitin-glucan complex (CGC) was used for the first time for the preparation of hydrogels. Alkali solvent systems, NaOH and KOH solutions, either at 1 or 5 mol/L, were used for CGC dissolution using a freeze-thaw procedure (freezing at −20 °C and thawing at room temperature; four cycles). The CGC solutions thus obtained were subjected to dialysis that induced the spontaneous gelation of the biopolymer, yielding translucid hydrogels with a yellowish coloration. Although all CGC hydrogels exhibited porous microstructures, high water content (above 97%) and good mechanical properties, their morphology, viscoelastic properties and texture were influenced by the type of solvent system used for CGC dissolution, as well as by their ionic strength. The K-based hydrogels presented a less compact network with larger pores and exhibited lower elastic properties. The Na-based hydrogels, on the other hand, exhibited a denser structure with smaller pores and a stiffer gel structure. These results show that it is possible to prepare CGC hydrogels with differing characteristics that can be suitable for different applications. Furthermore, all hydrogels were non-cytotoxic towards L929 fibroblasts and HaCaT keratinocytes. This study demonstrates CGC can be used to prepare biocompatible hydrogels with properties render them promising biomaterials